The Potential for Regional Express Trains when Introducing High‐speed Operation - Landex, Alex (Proceedings from the Annual Transport Conference at Aalborg University, 2009)
To operate faster trains it is likely that the capacity has to be improved. The improvements can be done by changing the operation, the procedures and/or the rolling stock. However, often it is necessary to improving the capacity of the railway by increasing the number of tracks, it is often discussed if the new tracks should be built along the existing railway line or a new railway line should be built. This paper examines the two possibilities regarding to a capacity perspective, increased speed, and possible changes in the route network. More trains can be operated with a homogeneous operation compared to a heterogeneous operation. However, operation with fast Intercity Express and Intercity trains, and slower regional and freight trains leads to a heterogeneous operation if the different train classes are not operated on separate tracks – alternatively the fastest trains have to be slowed down. Different railway lines for fast and slower train operation results in an approximately homogeneous operation and thus more capacity. The extra capacity can be used to operate more (regional) trains on the existing railway line, better service for long distance commuters by having skip stop services, and/or regular interval timetables. Furthermore, the new railway lines for high-speed operation can very often improve the service of the regional trains by introducing regional express trains operating on these lines.